Opportunistic Theft at Traffic Accident Scenes and the Limits of Victim Protection in Indonesian Criminal Law Enforcement - Moch Aji Surya Pamungkas; Dossy Iskandar Prasetyo (Fakultas Hukum Universitas Bhayangkara Surabaya, 2024)
Traffic accidents in Indonesia frequently create conditions of vulnerability that are exploited by opportunistic individuals to commit theft against incapacitated victims, constituting aggravated theft under Article 363 of the Indonesian Criminal Code (Kitab Undang-Undang Hukum Pidana/KUHP). This study examines the law enforcement process against such offenses within the jurisdiction of Polres Gresik and identifies the factors that influence its effectiveness. An empirical juridical method with a socio-legal approach was employed, combining semi-structured interviews with law enforcement personnel from Unit Laka Lantas and Unit Reskrim of Polres Gresik with secondary data drawn from relevant legislation, institutional reports, and academic literature. The findings indicate that while enforcement procedures formally conform to the applicable legal framework, operational effectiveness is significantly constrained by limitations in personnel capacity, inadequate surveillance infrastructure, low levels of community legal awareness, and fragmented inter-agency coordination between police, transportation authorities, hospital services, and Jasa Raharja. In response, Polres Gresik has undertaken institutional improvements including rapid response unit deployment, officer training programs, and community legal education initiatives, though these measures remain insufficiently institutionalized to produce durable enforcement outcomes. The study concludes that achieving consistent legal protection for accident victims requires simultaneous reform across personnel development, surveillance infrastructure, community legal literacy, and inter-agency information management, guided by an integrated institutional framework that bridges the gap between formal procedural compliance and substantive enforcement effectiveness.